Pendidikan Karakter Dalam Antologi Wacan Bocah Basa Jawa Sithik Edhing Karya Zuly Kristanto (Teori Resepsi Sastra) - Aditya, Aqmal Dandung; Hasan, Latif Nur (Jurnal Online Baradha, 2023)
The anthology of children's stories Sithik Edhing by Zuly Kristanto is one of the special readings for children, also contains many good lessons for children, especially about character education. Character education is one of the important lessons for children's development. This research will emphasize the importance of character education in children's stories. To find out the reader's point of view, this research uses the theory of literary reception described by Wolfgang Iser. The essence of this research is about the role of character education and opinions according to the reader's attitude. The purpose of this study is to clarify and explain the depiction of character education and opinions according to the reader's attitude towards the anthology of children's stories Sithik Edhing. The method used is descriptive qualitative method, and the data collection is by means of interviews and questionnaires. The recipients are fifth grade students of MI Nyi H. Ashfiyah having a total of 28 children. The results of interviews and questionnaires are opinions about the attitudes of readers, the data that has been obtained is grouped based on their responses. The results of this study, namely all receptors can respond, capture, and understand what goes into children's reading of the depiction of character education, namely: (1) Responsibility, (2) Honesty, (3) Religion, (4) Self-confidence, (5) Discipline, (6) Hard work, (7) Care, (8) Curiosity. Keyword : Character education, wacan bocah, literary reception, children's literature Antologi cerita anak Sithik Edhing karya Zuly Kristanto merupakan salah satu bacaan khusus untuk anak-anak, juga memuat banyak pelajaran yang baik untuk anak-anak khususnya tentang pendidikan karakter. Pendidikan karakter merupakan salah satu pelajaran penting bagi perkembangan anak. Penelitian ini akan menegaskan pentingnya pendidikan karakter dalam cerita anak. Untuk mengetahui sudut pandang pembaca, penelitian ini menggunakan teori resepsi sastra yang dijelaskan oleh Wolfgang Iser. Inti dari penelitian ini adalah tentang peran pendidikan karakter dan pendapat sesuai dengan sikap pembaca. Tujuan dari penelitian ini adalah untuk memperjelas sekaligus menjelaskan penggambaran pendidikan karakter dan pendapat sesuai dengan sikap pembaca terhadap antologi cerita anak Sithik Edhing. Metode yang digunakan adalah metode deskriptif kualitatif, serta pengumpulan datanya dengan cara wawancara dan angket. Penerimanya adalah siswa Kelas V MI Nyi H. Ashfiyah memiliki total 28 anak. Hasil wawancara dan kuisioner adalah pendapat tentang sikap pembaca, data yang telah diperoleh dikelompokkan berdasarkan tanggapannya. Hasil penelitian ini, yaitu semua reseptor dapat merespon, menangkap, serta memahami apa yang masuk ke dalam pembacaan anak terhadap penggambaran pendidikan karakter, yaitu : (1) Tanggung jawab, (2) Jujur, (3) Religius, (4) Percaya diri, (5) Disiplin, (6) Kerja keras, (7) Peduli, (8) Keingintahuan. Kata Kuci : Pendidikan karakter, wacan bocah, resepsi sastra, sastra anak